The Children's Crusade - Dickson, G. author. aut Link
XVII, 246 p.
Keywords: The Children's Crusade was possibly the most extraordinary event in the history of the crusades. The first modern study in English of this popular crusade sheds new light on its history and offers new perspectives on its supposedly dismal outcome. Its richly re-imagined history and mythistory is explored from the thirteenth century to present day.